Growth of Literacy in Kerala: State Intervention, Missionary Initiatives and Social Movements - E. T. Mathew (Economic and Political Weekly, 1999)
Contrary to the widely-held view which gives 'enlightened' native princes much of the credit fo widespread of literacy in Kerala, the educational transformation of that part of the country was t mainly by Christian missionaries (19th century) and movements for the uplift of deprived communities half of 20th century)